The Old Dominion and the New Nation : 1788-1801 - Beeman, Richard R. (Book collections on Project MUSE., 2015)
This comprehensive study -- an honorable mention in the 1971 Frederick Jackson Turner Award competition -- traces the emergence and development of the Republican and Federalist party organizations in Virginia and shows how the old oligarchic system based on wealth, influence, and social prestige remained strong in that state after the formation of the new nation. The book covers details of the Virginia Antifederalists' continuing hostility to the federal Constitution, James Madison's switch from the Federalist party to the emerging Republican party, Madison's and Jefferson's attempts to coordi.